Literature Review of Pharmacological Treatments for Neonatal Abstinence Syndrome - Indri, Indri; Ivanna, Ivanna (International Medical Journal Corp. Ltd, 2024)
Background: The literature on pharmacological treatments for Neonatal Abstinence Syndrome (NAS) underscores the complexity of managing this condition, which arises from in utero opioid exposure. The reviewed articles collectively emphasize the necessity of pharmacological interventions while advocating for a multifaceted approach that includes both pharmacological and non-pharmacological strategies to optimize outcomes for affected infants. Literature Review: Overall, the literature reflects a consensus on the necessity of pharmacological interventions for NAS while also emphasizing the importance of individualized treatment strategies that incorporate both pharmacological and non-pharmacological measures to optimize outcomes for affected infants. Conclusion: In conclusion, the literature indicates a consensus on the necessity of pharmacological interventions for NAS, while also emphasizing the importance of integrating non-pharmacological measures to enhance treatment outcomes. The ongoing dialogue about optimizing treatment protocols, exploring alternative pharmacotherapeutic agents, and addressing the long-term implications of these interventions remains critical as the prevalence of NAS continues to rise in the context of the opioid crisis.